Ultrasound- or Nerve Stimulation-Guided Wrist Blocks for Carpal Tunnel Release: A Randomized Prospective Comparative Study. Issue 4 (1st June 2008) - Macaire, Philippe; Singelyn, François; Narchi, Patrick; Paqueron, Xavier
Abstract : Background and Objectives: : We hypothesized that ultrasound-guided wrist blocks may be faster to perform, and may increase success rate, compared with nerve stimulation-guided wrist blocks. Methods: : Sixty patients undergoing ambulatory endoscopic carpal tunnel release were randomly allocated to receive median and ulnar nerve blocks using either sensory-motor nerve stimulation (n = 30) or ultrasound guidance (n = 30). Four mL of mepivacaine 1.5% was injected around each nerve. Performance time and onset time of complete sensory block were assessed. Results: : Median time to perform both median (ultrasound, 55 [48-60] vs. nerve stimulation, 100 [65-150] seconds, P = .002) and ulnar (ultrasound, 57 [50-70] vs. nerve stimulation, 80 [60-105] seconds, P = .02) nerve blocks were significantly shorter in the ultrasound group. Onset time of complete sensory block in the median (ultrasound, 370 [278-459] vs. nerve stimulation, 254 [230-300] seconds, P = .02) and ulnar (ultrasound, 367 [296-420] vs. nerve stimulation, 241 [210-300] seconds, P = . 01) nerve areas were shorter in the nerve stimulation group. The success rate was 93% in both groups. Conclusions: : This randomized prospective study demonstrates that ultrasound-guided wrist nerve blocks are as efficient as those performed with nerve stimulation.